The Improvement of Children 5-6 Years Gross Motoric Skill by Challenge Board Game in Mutiara Ibunda Islamic Kindergarten Semarang City - Khusnul Khotimah, Ari; Latiana, Lita (Jurusan PGPAUD FIP UNNES, 2021)
This study aims to determine whether there is an improvement in gross motoric skills of children aged 5-6 years in Islamic Kindergarten Mutiara Ibunda Semarang through a challenge board game. This type of research uses experiments with one group pretest-posttest design. The population in this study is all kindergarten students in Dabin (fostered area) IV Bulu Lor Sub-District, North Semarang District with limited outdoor area of 230 students, while the sample is done by purposive sampling technique that is group B students of Islamic Kindergarten Mutiara Ibunda as many as 30 students. The data collection method uses questionnaires, documentation, while technical data analysis consists of descriptive analysis, hypothesis testing through paired sample t-test and percentage techniques. Based on statistical calculations using paired sample t-test obtained t count > t table (17,486 > 2,045) and p value < 0.05 (0.000 < 0.05), then H1 is accepted. The calculations result of the percentage of gross motoric skills of children increased by 15.74% between pretest and posttest. The results of the study stated that there was an increase in gross motor skills of children aged 5-6 years after being given treatment through a challenge board game. This research is expected to contribute knowledge in developing children's gross motor skills and for teachers to be able to create more creative games by utilizing indoor areas to optimize the gross motor skills of children aged 5-6 years.